The staff of the education inspectorate of the Spanish Autonomous Communities in the 2007-2013 period - Peña Simón, José Ignacio (Avances en Supervisión Educativa, 2013)
One of the main contributions to get to know the state of Education Inspectorates in the different Autonomous Regions of Spain is the one that is being carried out by ADIDE-Federation Board. This research work on several aspects related to the profession such as the number of members of the Inspectorate, income or work conditions takes place from time to time. These studies allow us to see up close the outstanding features and differences among the previously mentioned regional education inspectorates.The research dealt with in this article is about the state of the staff of the different Spanish regional education inspectorates. The aim is to get to know, on one hand the percentage of education inspectors without permanent civil servant status and on the other the degree of the observance of the objectives of the 2007 gender equality Law as far as the female education inspectors is concerned regarding the whole staff. It is equally interesting to find out the effect of the adjustment and cutback policies carried out by the whole regional education public administrations to a greater or lesser extent, regarding the education inspectorate staff. The survey tries to compare the number of education inspectors in 2007, the year before of the beginning of the economic crisis, and the present year 2013 that is about to conclude.